2011
DOI: 10.1146/annurev-food-022510-133656
|View full text |Cite
|
Sign up to set email alerts
|

Food Components with Anti-Obesity Effect

Abstract: Although many food components are reportedly beneficial to body-weight management, lack of understanding of molecular mechanisms and their function in overall adiposity under physiological conditions hinders successful and safe development of antiobesity functional foods. A positive energy balance resulting from an increase in food intake, a reduced energy expenditure, and/or dysfunction of adipose biology is associated with the development of obesity. This article provides an overview of the components involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 150 publications
1
28
0
Order By: Relevance
“…Among a growing number of bioactive polyphenols, Nobiletin (NOB) is a citrus-derived dietary flavonoid with diverse physiological functions [4043]. More recently, NOB has been shown to display a protective role against high-fat diet (HFD)-induced obesity and other metabolic dysfunctions [4446].…”
Section: Resultsmentioning
confidence: 99%
“…Among a growing number of bioactive polyphenols, Nobiletin (NOB) is a citrus-derived dietary flavonoid with diverse physiological functions [4043]. More recently, NOB has been shown to display a protective role against high-fat diet (HFD)-induced obesity and other metabolic dysfunctions [4446].…”
Section: Resultsmentioning
confidence: 99%
“…Given the high prevalence of obesity and its associated threat to public health, it is critical to develop effective methods to prevent the development of obesity and/ or reverse obesity-related metabolic disorders. There is growing evidence that various dietary bioactive compounds confer protection from diet-induced obesity and insulin resistance in animals through attenuation of adipose tissue development and lipid metabolism (Baboota et al, 2013;Kim & Park, 2011;Patel, 2015;Yu, Cai, Zhang, Feng, & Huang, 2015). However, poor water solubility, instability in the gastrointestinal tract, and low bioavailability of many of these compounds limit their application to dietary control of human obesity.…”
Section: Introductionmentioning
confidence: 99%
“…The biochemical pathways involved in these processes are coordinated by the central nervous system (83)(84)(85)(86)(87). Normally, these biochemical pathways are highly regulated to maintain an optimum body weight and composition, with the amount of calories consumed balancing the amount of calories expended.…”
Section: Hormonal and Neurological Responsementioning
confidence: 99%
“…reducing appetite and food intake has also been shown to increase as their chain length decreases (93,131,(135)(136)(137)(138) and their unsaturation increases (139). Consumption of appreciable quantities of CLA has been shown to reduce body fat (87,140,141). However, a meta-analysis of randomized clinical trials in humans showed that this effect is relatively small and of uncertain clinical significance (142).…”
Section: Figure 12mentioning
confidence: 99%